Enhancer of zeste homolog 2 epigenetically silences multiple tumor suppressor microRNAs to promote liver cancer metastasis - Au, Sandy Leung-Kuen; Wong, Carmen Chak-Lui; Lee, Joyce Man-Fong; Fan, Dorothy Ngo-Yin; Tsang, Felice Hoching; Ng, Irene Oi-Lin; Wong, Chun-Ming (Hepatology (Baltimore, Md.), 2012)
Epigenetic alterations and microRNA (miRNA) deregulation are common in hepatocellular carcinoma (HCC). The histone H3 lysine 27 (H3K27) tri‐methylating enzyme, enhancer of zeste homolog 2 (EZH2) mediates epigenetic silencing of gene expression and is frequently up‐regulated in human cancers. In this study we aimed to delineate the implications of EZH2 up‐regulation in miRNA deregulation and HCC metastasis. Expressions of a total of 90 epigenetic regulators were first determined in 38 pairs of primary HCCs and their corresponding nontumorous livers. We identified EZH2 and its associated polycomb repressive complex 2 (PRC2) as one of the most significantly deregulated epigenetic regulators in primary HCC samples. Up‐regulation of EZH2 was next confirmed in 69.5% (41/59) of primary HCCs. Clinicopathologically, EZH2 up‐regulation was associated with HCC progression and multiple HCC metastatic features, including venous invasion (P = 0.043), direct liver invasion (P = 0.014), and absence of tumor encapsulation (P = 0.043). We further demonstrated that knockdown of EZH2 in HCC cell lines reduced the global levels of tri‐methylated H3K27, and suppressed HCC motility in vitro and pulmonary metastasis in a nude mouse model. By interrogating the miRNA expression profile in EZH2‐knockdown cell lines and primary HCC samples, we identified a subset of miRNA that was epigenetically suppressed by EZH2 in human HCC. These included well‐characterized tumor‐suppressor miRNAs, such as miR‐139‐5p, miR‐125b, miR‐101, let‐7c, and miR‐200b. Pathway enrichment analysis revealed a common regulatory role of these EZH2‐silenced miRNAs in modulating cell motility and metastasis‐related pathways. Our findings suggest that EZH2 exerts its prometastatic function by way of epigenetic silencing of multiple tumor suppressor miRNAs. Conclusion: Our study demonstrated that EZH2 epigenetically silenced multiple miRNAs that negatively regulate HCC metastasis. (HEPATOLOGY 2012)